1994
DOI: 10.1002/ajh.2830470106
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent RhGM‐CSF does not offset myelosuppression from intensive chemotherapy: Randomized placebo‐controlled study in childhood acute lymphoblastic leukemia

Abstract: To determine whether recombinant human granulocyte-macrophage colony-stimulating factor (rhGM-CSF) can offset the myelosuppressive effects of intensive chemotherapy, we carried out a double-blind placebo-controlled trial in which 40 patients with acute lymphoblastic leukemia (ALL) were randomized into two groups of 20 each. One group received rhGM-CSF (5.5 micrograms/kg SC) coadministered with chemotherapy and the other, placebo coadministered with chemotherapy from day 5 to day 11 and from day 19 to day 25 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 20 publications
2
8
0
2
Order By: Relevance
“…This was in keeping with the study by Calderwood et al [17] which also failed to show any advantage in the use of Rh-GM-CSF given concomitantly with chemotherapy in 40 patients with poor-prognosis ALL undergoing intensi®cation therapy. Prophylactic use of G-CSF in the treatment of solid tumours in childhood has shown little bene®t.…”
Section: Discussionsupporting
confidence: 78%
“…This was in keeping with the study by Calderwood et al [17] which also failed to show any advantage in the use of Rh-GM-CSF given concomitantly with chemotherapy in 40 patients with poor-prognosis ALL undergoing intensi®cation therapy. Prophylactic use of G-CSF in the treatment of solid tumours in childhood has shown little bene®t.…”
Section: Discussionsupporting
confidence: 78%
“…Rescue therapy with a CSF accelerates neutrophil recovery by stimulating the growth of hematopoietic stem cells. However, it has been shown both in adults [36] and in children with ALL receiving intensive chemotherapy [37] that simultaneous administration of CSF with cytotoxic treatment is ineffective or may even result in an exacerbation of neutropenia and thrombocytopenia.…”
Section: Strategies To Protect Normal Tissue From Therapeutic Toxicitymentioning
confidence: 96%
“…Two randomised placebo-controlled studies have examined the eects of CSFs in a total of 72 children with ALL: neither G-CSF (10 lg/kg per day) nor GM-CSF (5 lg/kg per day) reduced the incidence of chemotherapy-associated infections [14,20]. However, a recent interim report of a randomised trial involving 34 children (aged 2±16 years) with high-risk ALL showed that G-CSF (5 lg/kg per day) administration between chemotherapy courses (total of 258 courses) was eective in reducing the incidence (17% vs. 40% with placebo, P 0.007) and duration (6.2 vs. 20.3 days, P 0.02) of febrile neutropenia, the number of culture-proven infections (8% vs. 15%, P 0.04), and duration of antibiotic administration (12.5 days vs. 20.9 days, P 0.02).…”
Section: Primary Prophylaxismentioning
confidence: 99%